Environmental impact of sediment-hosted stratiform iron deposits: an on-land vs. submarine tailing simulation. A study of the stratiform iron mineralization in Dunderland Valley. - Fagerheim, Birgitte Andrea (UiT Norges arktiske universitet, 2019)
This thesis studies possible environmental impacts of tailings from the stratiform iron deposits. The study was conducted on selected mineralized samples from the Dunderland Valley, Nordland, simulating on-land and submarine tailing disposal conditions. The Dunderland Valley mineralization is hosted by Neoproterozoic (Tonian, 800-730 Ma) meta-sedimentary sequence of the Caledonian Uppermost Allochthon. The main ore minerals are hematite and magnetite, with quartz and carbonates as principal gangue minerals. Locally, a manganese-rich mineralization occurs. The concentrations of sulphide in is low, with iron sulphides recorded mostly along contact of ore bodies and host rocks. The study combines determination of mineralogical and geochemical characteristics of three main types of ore mineralization and their behaviour in a kinetic column test (12 weeks; modified EPA method 1627) simulating: 1) non-buffered on-land; 2) carbonate-buffered on-land; 3) submarine conditions. Physicochemical properties (pH, redox potential (Eh) and conductivity) of the kinetic column leachates were measured after 24 h, 48h, 1 week, 2 weeks, 6 weeks and 12 weeks. The ore samples were analysed on major and trace element composition before and after the kinetic test to determine potential geochemical changes. Thin sections of the ore samples were exposed to similar conditions as the kinetic test to trace potential mineralogical reactions. Thermodynamic modelling was performed to determine speciation of iron and manganese in on-land and submarine conditions. Results showed that the ore samples contain mostly iron-oxides, manganese-silicates and silica, with trace values of copper in the hematite and magnetite samples, and cobalt, arsenic and antimony in the manganese rich sample. These elements are in stable mineral phases, therefore do not represent an environmental threat. Since the samples are characterized by a high Fe3+/Fe2+ ratio, negligible amounts of sulphide minerals and abundant carbonate content, their capability to generate acid ...